Faktor Risiko Pasien Coronavirus Disease-19 (Covid-19) - Saphira Murfi; Tri Umiana Sholeha; Rani Himayani (Medula, 2022)
Coronavirus disease-19 (Covid-19) is a disease caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus that has caused a worldwide pandemic and reached Indonesia in March 2020. This disease causes a various clinical manifestations from mild to severe, one of which also depends on risk factors that can exacerbate Covid-19 patients to the point of causing death. Risk factors that are often associated with Covid-19 diseases, such as age, race and ethnicity, gender, obesity, history of hypertension, chronic obstructive pulmonary disease (COPD), and diabetes mellitus. This is also related to the entry of viruses into the body that uses angiotensin-converting enzyme-2 (ACE-2), causing various risk factors to appear. This article is a literature review that was compiled using articles as references that were used between 2020-2022.